Means of entertainment and its types in Al Maghreb: (448-918 AH / 1056-1512 AD) - Hussein, Zahraa; Khabut, Sabah (Al-Adab Journal, 2023)
The holidays are an opportunity for Muslims to celebrate their prayers, especially because they are closely related to their Shariah, and the following gives them an opportunity to celebrate and promote themselves and exaltation, which distracts them for some time from the hardships and pressures of daily life. As for those who share them in the country from other religions, except those who have customs and traditions that are naturally different from the Muslims, then, as a result of their religion, we introduced to them the holidays, they got used to paying them and obtaining some consolation through them for the enjoyment of the soul, and this is what we will discuss and discuss about the importance of this exaltation. And its nature and impact on the Maghreb Islamic society in this world